2018
DOI: 10.1039/c8cc02317d
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of BN triple bonds by main group reagents

Abstract: We report two rare instances of an insertion into the strong (ca. 170 kcal mol-1) BN triple bond of iminoboranes. In the first, a silylene inserts into di-tert-butyliminoborane to form an iminosilane. In the second, the highly crowded iminoborane Ter-NB-TMP (TMP = 2,2,6,6-tetramethylpiperidyl, Ter = 2,6-(diphenylmethyl)-4-tert-butylphenyl) can be forced to react with Pip-CC-Pip (Pip = piperidyl) at 60 °C. The reaction product is the apparent result of Pip-CC insertion into the iminoborane BN bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…In 2018, the Braunschweig group described the insertion of two main group reagents into the B�N triple bond. [45] Isolable silylene 112 reacted with di-tertbutyliminoborane 24 smoothly to form the bicyclic silaimineborane 113 via total cleavage of the BN triple bond (Scheme 18a). Compound 113 features two typical BÀ N single bonds…”
Section: Cleavage Of Bn Triple Bondsmentioning
confidence: 99%
“…In 2018, the Braunschweig group described the insertion of two main group reagents into the B�N triple bond. [45] Isolable silylene 112 reacted with di-tertbutyliminoborane 24 smoothly to form the bicyclic silaimineborane 113 via total cleavage of the BN triple bond (Scheme 18a). Compound 113 features two typical BÀ N single bonds…”
Section: Cleavage Of Bn Triple Bondsmentioning
confidence: 99%
“…Aside from oxoboranes, iminoboranes (RBNR′) represent another type of multiple-bonded organoboron compounds and have been extensively investigated since the seminal works by Paetzold and Noth . With respect to the isoelectronic alkynes, iminoboranes display an increased reactivity toward self-oligomerization and intramolecular C–H activation because of the intrinsic polarity and relative weakness of the BN triple bond. , Therefore, such species are typically generated by vacuum gas-phase pyrolysis of (trimethylsilylamino)boron halides using specialized apparatuses . However, with the help of sterically bulky organyls on either side of the BN triple bond, a variety of monomeric iminoboranes IV have been isolated and structurally characterized (Chart c) .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Bertrand et al demonstrated the cyclic (alkyl)­(amino)­carbene (CAAC)-induced elimination of a trimethylsilyl halide of (Me 3 Si) 2 NBX 2 to give the haloiminoborane–carbene adduct II . The Braunschweig group isolated two carbene-coordinated iminoboranes III and IV through complexation between t BuBN t Bu and CAAC and N-heterocyclic carbene (NHC), respectively . Nevertheless, both III and IV are thermally unstable and decompose above −45 °C gradually.…”
mentioning
confidence: 99%